The Role of Loneliness in the Tendency to Use Social Networks among Senior High School Students in Tehran - A. Aeli; S. Tajik Esmaeili, Ph.D. (خانواده و پژوهش, 2022)
The purpose of this study was to examine the role of loneliness in the tendency to use social media among senior high school students in Tehran. The research method was survey. The statistical population of the study was comprised of all secondary school students in Tehran and the sample size was 384 according to Cochran’s formula. The sample was drawn based on multi-stage cluster sampling method. The research instruments included UCLA Loneliness Scale (Russell, Peplau & Cutrona, 1980) and a researcher-made questionnaire to measure social network orientation. It is worth mentioning that UCLA Loneliness Scale was translated into Persian by Shekarshekan and Mirdereikvand in 2008. A total of 384 questionnaires were distributed and 346 responses were obtained. The results revealed that there was a positive, significant relationship between emotional loneliness and tendency to use social networks (0.358*). Moreover, there was a positive, significant relationship between social loneliness and the tendency to use social networks (0.311**). The results of regression analysis indicated that emotional and social loneliness accounted for 36.5 and 11.7 percent of changes in social network tendency, respectively. The loneliness variable (in both emotional and social dimensions) could approximately predict 48.2% of the variance in tendency to the use social networks. Results of analysis of variance showed that emotional and social loneliness had a significant effect on the tendency to use social networks.